INNV-23. LIFESTYLE COACHING IS FEASIBLE AND IMPROVES PILOT OUTCOMES IN FATIGUED BRAIN TUMOUR PATIENTS: THE BT-LIFE (BRAIN TUMOURS, LIFESTYLE INTERVENTIONS, AND FATIGUE EVALUATION) MULTI-CENTRE, PHASE II RCT. (9th November 2020) - G Rooney, Alasdair; Hewins, William; Walker, Amie; Withington, Lisa; Mackinnon, Mairi; Robson, Sara; Green, Aimee; Anderson, Garry; Bulbeck, Helen; Cochrane, Carol; Gillespie, David; Hewitt, Christopher; et al.
Abstract: BACKGROUND: Fatigue is common and disabling for brain tumour patients. We studied the feasibility of two innovative lifestyle coaching interventions for high fatigue. METHODS: Multi-centre phase II feasibility RCT (ISRCTN17883425). Adult primary brain tumour outpatients reporting significant fatigue (Brief Fatigue Inventory [BFI] score 4+), were randomised to one of three arms: Control; Health Coaching ("HC", comprising eight structured coaching sessions on lifestyle behaviours); or HC plus Activation Coaching ("HC+AC", adding two structured interviews targeting motivation to change). Outcomes were measured at baseline (T0), after interventions (T1), and at 16 weeks (T2). The primary outcome of feasibility was required for both recruitment (aim: average n= 5 fatigued patients recruited/month) and retention (aim: minimum 60% retention at T2). Secondary pilot outcomes included change in fatigue, depressive symptom, and QOL measures. RESULTS: Over a nine-month recruitment period, n= 46 fatigued brain tumour patients were recruited (average n=5.1/month) and n= 34 were retained to endpoint (retention at T2= 73%), meeting the primary outcome of feasibility. Surprisingly, fatigue reduced significantly after HC (T1 mean change in BFI score from T0 baseline, relative to the equivalent change in control group: HC= -2.3 points [95%CI -3.4/-0.3]; HC+AC= -2.0 [-2.9/+0.1]; ANOVA p= 0.02) and was reduced in magnitude in both intervention groups at T2 (p= N.S). Both interventions also improved depressive symptoms (T1 mean change in HADS-Depression: HC= -2.0 points [-5.6/-0.1]; HC+AC= -2.9 [-6.5/-1.0]; Kruskal-Wallis p= 0.02). Patient-nominated QOL outcomes improved persistently after HC+AC (T2 mean change in PSYCHLOPS score: HC= -2.4 points [-5.4/+2.8]; HC+AC= -6.1 [-9.2/-0.8]; ANOVA p= 0.01). CONCLUSION: Innovative coaching interventions, focused on lifestyle factors, are feasible to deliver to fatigued brain tumour patients. Preliminary signals suggest that these non-drug approaches may benefit several mediators of quality of life and warrant further study.